Revisão sistemática da literatura: a utilização do ácido acetilsalicílico AAS e cálcio como meio de prevenção para o desenvolvimento de pré-eclâmpsia em gestantes suscetíveis - MOURA, Darwin Ciro Nascimento de (2024)
This integrative literature review aims to carry out a literature review on “The use of acetylsalicylic acid AAS and calcium as a means of preventing the development of preeclampsia in susceptible pregnant women”, presenting the outcome regarding the prophylactic use of these substances. For the present study, a bibliographical survey was used for the period from 2017 to 2023 on the platforms Google academic (scholar), Pubmed, Virtual Health Library (VHL), Sciencedirect, Embase, Scielo and Scopus, using the keywords: Pre-eclampsia, Disease prevention, Aspirin or AAS and Calcium, for the selection of articles on the appropriate platforms. Articles were selected after reading the titles, abstracts and then reading the most relevant projects in full on the general theme, analyzing the material produced through tabulation and selection of articles according to theme; author; year; magazine; synthesis and main results. The articles were organized in chronological order, presenting the approaches carried out in each study, among the results obtained, the effectiveness of the use of aspirin and calcium as a preventive means for the development of Pre-eclampsia (PE) can be observed. Based on the results, it is concluded that the study on the use of ASA and calcium as a means of preventing the onset of PE in susceptible pregnant women has good efficacy as a prophylactic means when used early.